Digital innovation : Implementation of interactive teaching materials for vocational school teachers to support Merdeka Belajar and SDGs 4 - Azizah, Nuril Lutvi; Cornelius, Cornelius; Eviyanti, Ade; Liansari, Vevy; Wardani, Gita; Diba, Naila Farah (Universitas Muhammadiyah Magelang, 2025)
The problem in vocational school (SMK) learning is the lack of interactive teaching media used by educators. However, under the Merdeka Belajar curriculum, vocational school students are expected to develop their achievements and create self-employment opportunities based on their acquired skills. This activity aims to enhance the skills of vocational school teachers in digitizing teaching materials through 2D animated videos, 3D animated videos with Artificial Intelligence (AI), and digital flip books. The method used in this community service includes socialization, training, mentoring, and evaluation. The results of the activity indicate an improvement in vocational school teachers' skills in creating 2D and 3D animated instructional videos. Additionally, some teachers have successfully developed interactive digital-based teaching materials.